Characterization of Aeromonas hydrophila Wound Pathotypes by Comparative Genomic and Functional Analyses of Virulence Genes - Christopher J. Grim (American Society for Microbiology, 2013)
ABSTRACT Aeromonas hydrophila has increasingly been implicated as a virulent and antibiotic-resistant etiologic agent in various human diseases. In a previously published case report, we described a subject with a polymicrobial wound infection that included a persistent and aggressive strain of A. hydrophila (E1), as well as a more antibiotic-resistant strain of A. hydrophila (E2). To better understand the differences between pathogenic and environmental strains of A. hydrophila, we conducted comparative genomic and functional analyses of virulence-associated genes of these two wound isolates (E1 and E2), the environmental type strain A. hydrophila ATCC 7966T, and four other isolates belonging to A. aquariorum, A. veronii, A. salmonicida, and A. caviae. Full-genome sequencing of strains E1 and E2 revealed extensive differences between the two and strain ATCC 7966T. The more persistent wound infection strain, E1, harbored coding sequences for a cytotoxic enterotoxin (Act), a type 3 secretion system (T3SS), flagella, hemolysins, and a homolog of exotoxin A found in Pseudomonas aeruginosa. Corresponding phenotypic analyses with A. hydrophila ATCC 7966T and SSU as reference strains demonstrated the functionality of these virulence genes, with strain E1 displaying enhanced swimming and swarming motility, lateral flagella on electron microscopy, the presence of T3SS effector AexU, and enhanced lethality in a mouse model of Aeromonas infection. By combining sequence-based analysis and functional assays, we characterized an A. hydrophila pathotype, exemplified by strain E1, that exhibited increased virulence in a mouse model of infection, likely because of encapsulation, enhanced motility, toxin secretion, and cellular toxicity. IMPORTANCE Aeromonas hydrophila is a common aquatic bacterium that has increasingly been implicated in serious human infections. While many determinants of virulence have been identified in Aeromonas, rapid identification of pathogenic versus nonpathogenic strains remains a challenge for this genus, as it is for other opportunistic pathogens. This paper demonstrates, by using whole-genome sequencing of clinical Aeromonas strains, followed by corresponding virulence assays, that comparative genomics can be used to identify a virulent subtype of A. hydrophila that is aggressive during human infection and more lethal in a mouse model of infection. This aggressive pathotype contained genes for toxin production, toxin secretion, and bacterial motility that likely enabled its pathogenicity. Our results highlight the potential of whole-genome sequencing to transform microbial diagnostics; with further advances in rapid sequencing and annotation, genomic analysis will be able to provide timely information on the identities and virulence potential of clinically isolated microorganisms.